Aksjonsforskning i Norge: Teoretisk og empirisk mangfold - Gjøtterud, Stein; Hiim, Hilde; Husebø, Dag; Jensen, Liv Helene; Steen-Olsen, Tove Herborg; Stjernestrøm, Else (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2017)
Action Research in Norway. Theoretical and empirical diversity is an anthology consisting of twenty scientific articles from the fields of education, health, science centers, arts and working life. The anthology provides an insight into historical development, basic principles and theoretical and methodological discussions within the field of action research. The book addresses questions about participation, experience and dialogue as a basis for knowledge development. It includes topics such as professional development, development of school subjects, practice development, and organizational development. The empirical articles emphasizes on bridging the gap between theory and practice to understand, change and develop practices. Questions about the researcher´s role in action research are brought to attention, by highlighting issues such as the researcher's responsibility to contribute to reflection and clarification, and to raise critical questions, as well as to ensure that all voices are being heard. Furthermore, the anthology shows how exploratory methods, self-study and research in one's own organization can contribute to learning and knowledge creation. The anthology underscores the importance of developing good education in action research at Master and Ph.D. level and argues for the importance of strengthening the research teaching in this field. Overall, the anthology shows how action research as a research tradition contributes to clarify and develop its epistemological and methodological foundation, to provide valid research results and to convey relevant and credible new knowledge. Such knowledge has an impact on how we practice, communicate and understand research in a variety of contexts.